Metalloradical reactivity, charge transfer, and atom abstractions in a t-shaped iron(I) complex - Ott, Jonas C.; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2021)
A study of the reactivity of a T-shaped iron(I) complex supported by a carbazole-based PNP pincer ligand (1) has established its strongly reducing character and propensity to bind small molecules with concomitant transfer of charge and spin density. Metalloradical reactivity was observed in the reaction with the stable radical 2,2,6,6-tetramethylpiperidinyloxyl (TEMPO) yielding the corresponding FeII hydroxylaminato complex 2. Complex 1 reacted rapidly and selectively with two molecules of carbon monoxide to give the corresponding low-spin dicarbonyl complex 3. When reacted with phenylacetylene, the alkyne complex 4 was isolated in which the alkyne was found to bind side-on as an η2-ligand, which adopts radical anion character as a result of charge transfer from the metal center. Reaction with diphenyl diazomethane generated an adduct 5 in which the diazoalkane also appears to be partially reduced and acquires radical character. Upon exposure to carbon dioxide, oxygen atom abstraction was observed, ultimately leading to the isolation of the monocarbonyl iron(I) complex 6 and a dinuclear carboxylato ferrous complex 7. Furthermore, reaction with chalcogen atom transfer reagents resulted in the formation of the corresponding dinuclear ferrous chalcogenido compounds (E = S (8), Se (9)), which were found to display strong antiferromagnetic coupling (8, JAFC = −68 cm-1; 9: JAFC = −58 cm-1).
Gesehen am 04.05.2021